Relationship between malocclusion and deleterious oral habits in preschool children in Campina Grande, PB, Brazil - Cavalcanti Leite Alessandro; Bezerra Medeiros Kelly Priscila; Moura Cristiano; Bezerra Medeiros Priscilla; Granville-Gracia Flávia Ana (Serbian Medical Society - Dental Section, Belgrade, 2008)
Purpose: To evaluate the prevalence of malocclusions in preschool children in the city of Campina Grande, PB, Brazil, and verify the existence of associations between malocclusions and deleterious oral habits, gender and age. Methods: 342 children (3-5-year-old; 196 boys and 146 girls) with complete primary dentition and no previous orthodontic treatment were randomly selected from children regularly attending municipal day care centers. The occurrence of the following malocclusions was evaluated: accentuated overjet and overbite, anterior open bite and posterior crossbite. A calibrated experienced examiner (Kappa = 0.86) performed all clinical examinations under natural lightening after drying the teeth and soft tissue with gauze. Yates' chi-square and Fisher's exact tests verified the association between the variables and odds ratio. Significance level was set at 5%. Results: Malocclusions and deleterious oral habits were observed in 74% and 73.4% of the children, respectively. The prevalence of malocclusion was 68.9% in boys and 80.9% in girls. Accentuated overjet (45%) and anterior open bite (42.4%) were the most prevalent malocclusions. There was statistically significant difference (P = .008) between genders. However, no statistically significant differences (P = .47) were found among the age groups. Accentuated overjet, anterior open bite and posterior crossbite showed a positive association with the presence of deleterious oral habits. Conclusions: The high prevalence of malocclusions and deleterious oral habits observed in this pediatric population is supportive to the fact that oral health professionals that treat patients in these age groups should be aware of the importance of an early and accurate diagnosis in order to avoid the aggravation of occlusal alterations in the future.